Do patients whose psychogenic non-epileptic seizures resolve, 'replace' them with other medically unexplained symptoms? Medically unexplained symptoms arising after a diagnosis of psychogenic non-epileptic seizures. Issue 9 (18th March 2011) - McKenzie, Paul S; Oto, Maria; Graham, Christopher D; Duncan, Roderick
Abstract : Background: In clinical practice, it is sometimes observed that patients in whom psychogenic non-epileptic seizures (PNES) cease, develop another medically unexplained symptom (MUS). Methods: In order to determine how many patients develop new MUS post diagnosis and whether patients whose attacks cease are more likely to do so, new MUS were recorded 6–12 months after the diagnosis of PNES in 187 consecutive patients. Results: Compared with baseline, the overall proportion of patients with MUS increased slightly, from 70.1% to 76.5%, with 44/187 patients (23.5%) developing new MUS. There were no significant differences between attack free and non-attack free patients. Binary logistic regression analysis showed that predictors of new MUS diverged between attack free and non-attack free patients. Among patients continuing to have attacks, those with previous health related psychological trauma were 18.00 times more likely to develop new MUS (p<0.0005). In patients who became attack free, patients drawing disability benefits were 5.04 times more likely to have new MUS (p=0.011). Conclusions: The results suggest that almost 25% of patients develop new MUS following a diagnosis of PNES, although most of those have MUS pre-diagnosis. Patients with a history of health related psychological trauma whose attacks continue after diagnosis are at particularly high risk of developing new MUS. The data do not support the hypothesis that PNES that resolve are likely to be 'replaced' by other MUS.